x*2-7z+12=

Simple and best practice solution for x*2-7z+12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*2-7z+12= equation:


Simplifying
x * 2 + -7z + 12 = 0

Reorder the terms for easier multiplication:
2x + -7z + 12 = 0

Reorder the terms:
12 + 2x + -7z = 0

Solving
12 + 2x + -7z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + 2x + -12 + -7z = 0 + -12

Reorder the terms:
12 + -12 + 2x + -7z = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 2x + -7z = 0 + -12
2x + -7z = 0 + -12

Combine like terms: 0 + -12 = -12
2x + -7z = -12

Add '7z' to each side of the equation.
2x + -7z + 7z = -12 + 7z

Combine like terms: -7z + 7z = 0
2x + 0 = -12 + 7z
2x = -12 + 7z

Divide each side by '2'.
x = -6 + 3.5z

Simplifying
x = -6 + 3.5z

See similar equations:

| -99=-11p | | 6s+6=4s+12 | | 89=4v+17 | | y^4=625 | | 9x^2=81x | | 9=3(5-2d) | | 7(-5-8)=8(-8+13) | | 5s^3t^2[3s-5t^2]= | | 11x+28=4x+238 | | 11y-3y=48 | | 6s+6=8s-26 | | z^2+2z=20 | | s^2+5+6= | | (X-2)(x^2+5x-3)= | | 75+(z-1)y=90 | | 24=-6+(x-5) | | 4(p-6)=-32 | | y-11=-2.5(x+2) | | 122+c=327 | | x+90=3x | | 7(-5-13)=8(-13+13) | | y=4x^2-14x+6 | | k^2x-4kx-5=0 | | y=0.75(x+8)-9 | | -5(3x-5)=2(x-16)-45 | | 5x[7x^2-2x]= | | r-52=156 | | 12x(x-6)=2(x-9) | | y=sqrt((4x^2)-100) | | 5(4x+1)-9(2x-3)=38 | | 4(3x-2x)=15 | | 2x[5x^2-4]= |

Equations solver categories